Yersinia pestis acetyltransferase-mediated dual acetylation at the serine and lysine residues enhances the auto-ubiquitination of ubiquitin ligase MARCH8 in human cells. Issue 7 (3rd April 2017) - Li, Cuiling; Wang, Daoguang; Lv, Xin; Jing, Ruirui; Bi, Baibin; Chen, Xinjun; Guo, Jisheng; Wang, Fengqin; Sun, Shengnan; Azadzoi, Kazem M.; Yang, Jing-Hua
ABSTRACT: Lysine acetylation is known as a post translational modification (PTM) by histone acetyltransferases (HAT) that modifies histones and non-histone proteins to regulate gene expression. Serine acetylation, however, is reported in mammalian hosts by serine acetyltransferase of Yersinia pestis (YopJ) during infection. The protein target and cellular function of bacterial YopJ in mammalian systems are not fully addressed. Here we report dual acetylation at the serine and lysine residues by transiently expressed serine acetyltransferase YopJ mimicking Y. pestis infection in HeLa cells. Using shotgun proteomics followed by label-free quantification, we demonstrate an increase of dual acetylation in YopJ transfected human cells, including 10 Ser- (YopJ/non-YopJ 1.3-fold, p = 0.02) and 8 Lys- (YopJ/non-YopJ 3.5-fold, p = 0.00003) acetylation sites. Specifically, YopJ expression augments acetylation of membrane-associated E3 ubiquitin ligase MARCH8 at the serine residue Sac44, Sac71 and Sac253, and the lysine residue Kac247 and Kac252. YopJ-mediated Ser- and Lys-acetylation of MARCH8 is further confirmed by Western blotting using the specific antibodies against MARCH8 Sac71 and pan-acetyl lysine. Functional study demonstrates that YopJ-mediated Ser- and Lys-acetylation affects the auto-ubiquitination of MARCH8. The mutant C172A of YopJ previously shown to abolish the acetyltransferase activity also reduces Ser- and Lys-acetylation and diminishes the auto-ubiquitination of MARCH8. In support, MARCH8 is indeed acetylated at serine and lysine in vitro by purified YopJ but the activity is reduced by the C172A mutant in YopJ. Our study provides evidence that bacterial serine acetyltransferase YopJ mediates Ser- and Lys-acetylation and affects auto-ubiquitination of ubiquitin ligase MARCH8 in human cells.